Estimasi Produktivitas Serasah di Lahan Bera Womnowi, Distrik Sidey, Manokwari - Slamet Arif Susanto; Heru Joko Budirianto; Agatha Cecilia Maturbongs (Jurnal Ilmu Pertanian Indonesia, 2020)
Aspects of litter productivity in fallow land in Manokwari, Western Papua need to be investigated because litter has the potential to increase soil fertility. The objective of this research was to count and estimate litter productivity in 15 years-fallow land in Womnowi, Sidey District, Manokwari. We used litter trap of 1 m2 in size with 2 mm mesh size. Nine litter traps were set under tree species, three replications of each tree species which have higher Important Value Index (IVI). Litters were weekly taken and oven dried until reaching the constant mass. Result showed that the dry masses of litters are not significantly different among three species. If the productivities are constant and probabilities of litterfall are same, the estimates of Dractontomelon dao have dry mass productivity rate (DMP) reaching 10.32 ton ha-1 year-1, followed by 8.98 ton ha-1 year-1 for Pometia pinnata, and 7.96 ton ha-1 year-1 for Octomeles sumatrana. Dry mass percentage (DMP) decreased in the order of P. pinnata > D. dao > O. sumatrana. We found negative linear regressions about water content of litter (WCL) and DMP at P. pinnata and O. sumatrana, but not for D. dao. These negative linear regressions can be used to estimate the rate of decomposition of each species. Keywords: linear regression, litterfall, secondary forest, soil fertility, Western Papua